”Finsk sisu” og ”norsk” hoppmentalitet : Skiløping og skiftende kvensk minoritetsforståelse i fortellingene om ”finske” Per Olsen og ”hopperen” Bjørn Wirkola - Pedersen, Helge Chr. (Idrott, historia och samhälle, 2024)
Despite the importance of sport to society as a whole and to different minority groups, the role of sport in forming ethnic identities in the Nordic countries have not been thoroughly examined by academics. The historically diverse communities of orthern Norway, consisting of Kveens, Sámi and Norwegians has fostered great athletes. Skiers Per Olsen and Bjørn Wirkola from Alta are two of them who competed in the 1950s and 1960s respectively. They were both of partly Kveen heritage. This article investigates the shifting understanding of Kveen identity throughout the post-war period by analyzing media narratives about Olsen and Wirkola. This study shows how their Kveen identity was shaped by their personalities as well as how it evolved over time. The Kveen heritage was higlighted in the narratives of Olsen in the 1950s but not in the displays of Wirkola ten years later. Today, Wirkolas’ Kveen heritage is central to the understanding of his success as a Ski jumper.